The effect of systemic antibiotics on clinical and patient‐reported outcome measures of oral implant therapy with simultaneous guided bone regeneration. Issue 5 (17th February 2020) - Payer, Michael; Tan, Wah Ching; Han, Jie; Ivanovski, Saso; Mattheos, Nikos; Pjetursson, Bjarni E.; Zhuang, Longfei; Fokas, George; Wong, May C. M.; Acham, Stephan; Lang, Niklaus P.; ,
Abstract: Objectives: The aim of the present superiority study was to determine the effect of systemic antibiotics primarily on patient‐reported outcome measures (PROMs) and post‐surgical complications in patients undergoing oral implant therapy with simultaneous guided bone regeneration (GBR). Materials and Methods: A total of 236 medically and periodontally healthy patients received oral implants with simultaneous GBR at seven centres. Pre‐operative antibiotics of 2 g amoxicillin were prescribed to the test group 1 hr prior to surgery and 500 mg thrice daily on days 1–3 after surgery. The control group was given a placebo. Group allocation was performed randomly. Primary outcome variables were PROMs recorded as visual analogue scale scores assessed on days 1–7 and 14 on pain, swelling, haematoma and bleeding. Post‐operative complications as secondary outcome variables were examined at 1, 2, 4 and 12 weeks from surgery. Chi‐square tests and repeated measures of analysis of variance (ANOVA) were performed for statistical evaluation. Results: No statistically significant differences ( p  > .05) between the two groups were detected for the evaluated PROMs. The same was noted with respect to post‐surgical complications. Four implants were lost—three in the test group and one in the control group. Conclusion: In this trial, systemic antibiotics did not provide additional benefits to PROMs, nor the prevention of post‐surgical complications in medically and periodontally healthy patients undergoing oral implant therapy with simultaneous GBR. However, further studies with larger sample sizes are still required to support the clinical outcomes of this study.